Cardinal Ratzinger in Dialogue with the Toronto School of Theology: What Was Said in 1986? - Steinhauser, Michael G. (Toronto journal of theology, 2013)
A question-and-answer session on being a theologian of the Catholic Church. Topics include, for example, the theologian's responsibility to question claims of Church teachings by those in authority, development of the magisterium, methodology in critiquing of Scripture and use of doctrine, teaching of faith as authentic expression over and against theology as technical reflection, Eucharist and inter-communion, dissenting with retracting theological claims under duress, mysticism as substratum for theology to proposer, the idea of moral theology and the structure of dogmatic doctrine, and distinguishing between the Church's position and the opinion of the majority of theologians.